Analyzing the Effects of Transplanting and Direct Seeding on the Growth and Yields of Green Pepper. - Natukunda, Tracy (Kabale University, 2024)
In sub-Saharan Africa (SSA), smallholder-based agriculture is the main source of livelihood, especially in the rural areas, where most of the population lives. Vegetable production provides for high-value crops especially green pepper that can be raised on small pieces of land throughout the year and as such, many smallholder farmers have increasingly gained interest in them. The objective was to analyze the growth and yield performance of green pepper subjected to direct seeding and transplanting thus understanding its profitability and ultimately contributing to the income of the farmers in Kabale district. The experiment was laid out in a randomized complete block design (RCBD) of 10*10 with two treatments and their controls and replicated 2 times at Kabale University The treatments included subjecting one of the plots to transplanting while the other was subjected to direct seeding. The findings showed that plant height, number of branches, growth, and yield were greatly affected by the transplanting done during the production process hence enhanced productivity and more profits were generated from the same plots. Continuous research and collaboration among researchers, growers, and agricultural experts are essential for advancing our understanding of the effect of direct seeding and transplanting on the yields and quality production in green pepper production. The choice between transplanting and direct sowing can significantly impact the growth and yields of green peppers. Transplanting allows for better control over seedling development, early planting, and protection from adverse weather conditions. On the other hand, direct sowing can be more cost-effective and less labor-intensive. Understanding the effects of these two methods on green pepper growth and yields is crucial for optimizing production practices and ensuring a successful harvest.